An unlikely revolutionary : Matsuo Takabuki and the making of modern Hawai'i : a memoir - Takabuki, Matsuo, 1923- (Extraordinary lives., 1998)
"Anyone interested in understanding the last fifty years of Hawai'i's economic and political history would do well to examine the life of Matsuo "Matsy" Takabuki. Actively involved in the Democratic Party during the post-World War II years, Takabuki was among a generation of Americans of Japanese Ancestry to rise to political office in the 1950s. A confidant of Governor John Burns, a member of the Board of Supervisors of the City and County of Honolulu, a business associate of developer and financier Chinn Ho, a trustee of the Bishop Estate - Takabuki has been at the heart of many of the sweeping social, financial, and political changes that have fundamentally altered Hawai'i in the last half century. An Unlikely Revolutionary is Takabuki's own story, told in his characteristically straightforward manner, of his life and work as one of the "movers and shakers" behind Hawai'i's transformation from an isolated, agriculture-based territory to a highly diverse, competitive modern community."--Jacket